THE EFFECT OF THE APPLICATION OF PICTURE STORY DOMINOES (PSD) THROUGH GOOGLE CLASSROOM AND READING INTEREST TOWARDS THE EIGHTH GRADE STUDENTS’ READING ABILITY - Shena Aji Wahyuningrum (Esteem Journal of English Education Study Programme, 2022)
The purpose of this research was  to know the effect of the application of picture story dominoes (PSD) through Google classroom and reading interest towards the eighth grade students’ reading ability at junior high school 19 Palembang. Especially, the purpose of this study to determine the significant  effect of the application of picture story dominoes (PSD) through Google classroom and reading interest towards the eighth grade students’ reading ability at junior high school 19 Palembang. The method of this research is a quantitative factorial design method that consists of a set of students’ reading interest questionnaires and multiple choices reading test. The result showed that the application of picture story dominoes (PSD) through Google classroom and reading interest were effective on the eighth grade students’ reading ability.